TAFSIR AL-QUR’AN BAHASA MADURA - Kamil, Ahmad Zaidanil; Ramdhani, Fawaidur (Lajnah Pentashihan Mushaf Al-Qur'an, 2019)
Abstrak This paper studies the Qur'anic Interpretation (Quranic exegesis) of Nurul Huda by Mudhar Tamim (1916-2000). The focus that will be discussed in this paper is a brief history of the study of the Qur'an in Madura, methodological aspects of the interpretation, and critics presented by Mudhar Tamim against some of the socialreligious traditions of the Madurese community. It is by using a hermeneutic approach, the conclusionof this study shows that the Qur'anic Interpretation of Nurul Huda has given a new nuance in the history of the Qur'an studies in Madura. Historically, this interpretation (quranic exegesis) is the first Qur'anic study whose writing uses Latin script, both in the form of translation and interpretation. In terms of methodology, Mudhar Tamim adopted and applied the tahlīlī method. Through this lengthy analytical explanation, emerged the pattern of Islamic jurisprudence ( fiqh) and that of socio-community life. On some occasions, Mudhar Tamim presented constructive critics on the tradition of following something blindly and the practice of tariqah (religious brotherhood in sufism) which was developing at that time. As one of the Quranic interpretations work of a Muslim archipelago, that interpretation is important to be studied because it is able to contribute, at least to the enrichment of literature and discourse about the interpretation of the Qur'an in the archipelago.